Massive transfusion protocol - Tobi Ash (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2023)
Hemorrhage from trauma, surgery, obstetric emergencies, and gastrointestinal bleeds remain a cause of potentially preventable deaths for patients. However, transfusions of large amounts of blood products may lead to complications. The development of Massive Transfusion Protocols (MTP), a proactive treatment protocol to manage profound blood loss, has shown improved outcomes for patients requiring immediate and multiple blood transfusions. These guidelines help to recognize hemorrhagic patients in need of an MTP as well as how to best manage this complex protocol.